Rassuzhdeniya o dal'neishem issledovanii voproca polovogo dimorfisma v sporte - Drozdovski, Z. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
This study is centered on a problem of sexual dimorphism in sport, its influence to sports development and scientific researches in that field. The author gave a short excursus to history of the problem's analyzing in Poland, noted some preliminary results and outlined further tendencies in sexual dimorphism researching. At the end of the article the author suggested some organizational points to increase researching efficiency of the problem's solving.